Non-thyroidal illness syndrome and its relationship with mortality risk in critically ill children - Carreras, Laura; Riaño, Isolina; Vivanco, Ana; Avello, Noelia; Iglesias, Tania; Rey, Corsino (Frontiers in Pediatrics, 2023)
Introduction: Non-thyroidal illness syndrome (NTIS) is considered to be associated with adverse outcomes in critically ill children. The hypothesis that thyroid hormones and inflammatory markers are associated with increased prediction of mortality risk scores is tested in this paper. Methods: A prospective observational study was set up in a pediatric intensive care unit (PICU). One hundred and three patients were included. NTIS was defined as a low free triiodothyronine (FT3) value for the patient’s age. Thyroid hormones levels and inflammatory markers were determined at admission: FT3, FT4 (free thyroxine), TSH (thyroid-stimulating hormone), rT3 (reverse triiodothyronine), CRP (C-reactive protein) and PCT (Procalcitonin). They were compared between children with a pediatric risk of mortality score PRISM-III >75th percentile (group A, n=25) and the rest (group B, n=78). Results: A FT4 value lower than 16.6 pmol/L showed an area under the curve (AUC) of 0.655 (0.56-0.78, p=0.02), with 76% sensitivity and 61.5% specificity to detect a high risk of mortality. A multiple regression analysis revealed that a FT4 lower than 16.6 pmol/L (OR 4.92 (1.60-18.19), p=0.009) and having NTIS (OR 6.04 (1.45-27.93), p=0.016) could predict a high risk of mortality. Discussion: In unselected critically ill children, FT4 and FT3 values at admission could be used as a good predictor of a high mortality risk. We have not achieved a predictive model that combines hormones with inflammatory markers.